1940
DOI: 10.1152/ajplegacy.1940.129.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Effects on the Volume and Composition of Blood in Man

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1943
1943
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…A number of observations in man show that an increase in blood volume occurs during exposure to high environmental temperatures. Haomodilution is one of the earliest responses to heat, but prolonged exposure may increase total circulating hsemoglobin with return to normal concentrations in the blood [Bazett, Sunderman, Doupe and Scott, 1940;Post and Spealman, 1948]. If the porphyrin in the mouse Harderian gland can be mobilized for hamoglobin synthesis, it seems possible that an increase in blood volume in the heat may account for the increase in porphyrin production by the gland.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observations in man show that an increase in blood volume occurs during exposure to high environmental temperatures. Haomodilution is one of the earliest responses to heat, but prolonged exposure may increase total circulating hsemoglobin with return to normal concentrations in the blood [Bazett, Sunderman, Doupe and Scott, 1940;Post and Spealman, 1948]. If the porphyrin in the mouse Harderian gland can be mobilized for hamoglobin synthesis, it seems possible that an increase in blood volume in the heat may account for the increase in porphyrin production by the gland.…”
Section: Discussionmentioning
confidence: 99%
“…Calculated plasma volume is very closely related to plasma viscosity; therefore, correction factors based on calculated plasma volume are often used to assess hemoconcentration [7,32]. Early researchers assumed that, under conditions of constant red cell volume, a decrease in hematocrit corresponded to a proportionally equal increase in plasma volume [33,34]. Research in the 1970s, however, suggested that hematocrit and plasma volume were not as proportional as were earlier predicted [35], and therefore hematocrit has not been shown to be directly related to plasma volume.…”
Section: Hematocrit Hemoglobin and Plasma Volumementioning
confidence: 99%
“…However, this is also in part dependent on elevated food consumption and increased passage of material along the intestine. The extent of which the rapid passage might impair thyroid hormone reabsorption is not clear, (7,8,11,24,25,39).…”
Section: _mentioning
confidence: 99%